2022
DOI: 10.1007/s12020-022-03002-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes of gut microbiota in diabetic nephropathy and its effect on the progression of kidney injury

Abstract: Background: We aimed to illustrate gut microbiota and short chain fatty acid (SCFA) levels in diabetic nephropathy (DN) patients, and investigate the mechanism of sodium butyrate in diabetic mellitus (DM) rats.Methods: Gut microbiota and serum SCFA levels were measured by 16S rDNA and GC-MS respectively.After being built by streptozotocin (DM rats), the DM rats were administered 300mg/kg sodium butyrate for 12 weeks (DM+BU rats). Gut microbiota, serum and fecal butyrate level were measured. RT-PCR, WB and tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 46 publications
0
57
0
1
Order By: Relevance
“…Butyrate levels in serum were reduced in patients with DKD compared with patients with diabetic mellitus and healthy controls. Butyrate levels in serum were positively correlated with estimated glomerular filtration rate [65]. Treatment with butyrate could elevate butyrate levels in serum and faeces and inhibit glomerular area enlargement as well as intrarenal fibronectin and collagen IV expressions in the rats with diabetic mellitus [65].…”
Section: Iga Nephropathymentioning
confidence: 96%
See 3 more Smart Citations
“…Butyrate levels in serum were reduced in patients with DKD compared with patients with diabetic mellitus and healthy controls. Butyrate levels in serum were positively correlated with estimated glomerular filtration rate [65]. Treatment with butyrate could elevate butyrate levels in serum and faeces and inhibit glomerular area enlargement as well as intrarenal fibronectin and collagen IV expressions in the rats with diabetic mellitus [65].…”
Section: Iga Nephropathymentioning
confidence: 96%
“…Butyrate levels in serum were positively correlated with estimated glomerular filtration rate [65]. Treatment with butyrate could elevate butyrate levels in serum and faeces and inhibit glomerular area enlargement as well as intrarenal fibronectin and collagen IV expressions in the rats with diabetic mellitus [65]. Treatment with butyrate could increase LC3 messenger ribonucleic acid expression and LC3BII/I ratio in renal tissue of diabetic mellitus rats.…”
Section: Iga Nephropathymentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, Cai et al . also reported that the proportion of short chain fatty acids (SCFAs)-producing bacteria in gut microbiota was decreased in DKD patients, and the oral supplement of SCFAs could improve kidney injury in the diabetic mouse model ( 19 ). These studies suggested that targeting the gut microbiota could be a novel strategy for the prevention of DKD.…”
Section: Introductionmentioning
confidence: 99%